THE ROLE OF THE YOUNGER GENERATION IN BUILDING A DIGITAL-BASED CIVIL SOCIETY - Rizquna Salma Labibah; Ikhwan Imam Saputra (Tahta Media Group, 2025)
This study aims to analyze and evaluate the structural and cultural challenges faced by youth in building a digitally based civil society. The research employs a qualitative socio-legal approach with multiple case studies involving youth communities engaged in social advocacy, digital literacy initiatives, and intergroup dialogue through online platforms. Data were collected through in-depth interviews, digital observation, and analysis of recent policy documents and reports. The findings reveal that youth play significant roles as digital literacy advocates, facilitators of inclusive dialogue, mobilizers of online social action, and producers of narratives promoting pluralism and civic values. However, their effectiveness is constrained by structural challenges, including unequal internet access, limited critical digital literacy, sustainability of community funding, and evolving digital regulations. Cultural challenges such as identity polarization, sensational media culture, and intergenerational value gaps also affect the quality of public deliberation. The study concludes that building a digital civil society requires strengthened digital literacy, inclusive policy support, and cross-sector collaboration to ensure an ethical, participatory, and sustainable digital public sphere.